THE EFFECT OF REALITY ON THE QUALITY OF PHYSICS LEARNING IN COLLEGE STUDENTS: A CASE STUDY - Siahaan, Fine Eirene (JURNAL EDUCATION AND DEVELOPMENT, 2025)
Virtual Reality (VR) in physics education is an innovative approach that uses technology to create a more immersive and interactive learning experience. With VR, students can interact with complex physics simulations, which helps them understand difficult concepts in a more intuitive way. This study aims to determine the effect of Virtual Reality (VR) on the quality of physics learning of HKBP Nommensen University Pematangsiantar students. This research method with One Group Design or One Group Pretest-Posttest Design (experimental research where only one group is studied). This design involves two stages of measurement: before treatment (pretest) and after treatment (posttest). The sample used in this study consisted of 15 students from the Physics Education program in the 2023/2024 academic year. The instrument used in this study is in the form of questions in the form of essays with a total of 10 questions to measure the quality of learning, namely the cognitive results of students in experimental courses, where the indicators of cognitive start from C3-C6. This instrument will be used as a pretest and posttest to be given to the students, and also as a questionnaire in the form of a questionnaire to see the satisfaction of the students in using VR in learning. This questionnaire will be administered later along with the posttest. The results showed a significant increase in students' cognitive understanding, with an average pretest score of 73.00 and an average posttest score of 80.33, resulting in a t-test p-value of 0.00, rejecting the null hypothesis. The ANOVA results confirmed a significant difference in learning outcomes with a p-value also of 0.00. Student satisfaction with the use of VR was recorded as "excellent" at 4.00.